Childhood migration and educational attainment: Evidence from Indonesia - Hanna M. Schwank (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
Millions of families migrate every year in search of better opportunities. Whether these opportunities materialize for the children brought with them depends on the quality of the destination that their parents selected. Exploiting variation in the age of migration, I analyze the impact of destination quality on the educational outcomes of childhood internal migrants in Indonesia. Using Population Census microdata from 2000 and 2010, I show that children who spend more time growing up in districts characterized by higher average educational attainment among permanent residents tend to exhibit greater probabilities of completing primary and secondary schooling. Moreover, educational outcomes of migrants converge with those of permanent residents at an average rate of 1.7 to 2.2 percent annually, with children from less educated households benefiting more from additional exposure. My findings suggest substantial heterogeneity of returns to childhood migration with respect to destination.
Keywords: I25; O15; D64; 330; Internal Migration; Education; Development; Indonesia